Measurement of labor quality growth: Caused by unobservable characteristics - Mathias Zurlinden; Thomas Bolli (ETH Zurich, KOF Swiss Economic Institute, 2008)
The standard economy-wide indices of labor quality (or human capital) largely ignore the role of unobservable worker characteristics. In this paper, we develop a methodology for identifying the contributions of both observable and unobservable worker characteristics in the presence of the incidental parameter problem. Based on data for Switzerland over the period 1991-2006, we find that a large part of growth in labor quality is caused by shifts in the distribution of unobservable characteristics. The contributions to growth attributed to education and age are corrected downwards, if unobservable worker characteristics are taken into account. Yet the standard indices of labor quality appear to be robust to this extension.
Keywords: J24; J31; 330; human capital; labor quality; Humankapital; Arbeitsproduktivität; Indexberechnung; Schweiz